Digitania© or the disillusion with a digital citizenship - Sebastião, Sónia Pedro (2015)
This article is a theoretical contribution to the understanding of e-democracy, that is, of the efforts to broaden political participation and knowledge about citizenship using information and communication technologies. Digital citizenry practices are envisaged as an addition to traditional practices such as voting and party membership. Though digital environment is recognized as an important contribution to public life, its limits are also emphasized which implies to propose a realistic view about the existence (or not) of a new type of citizenship: digital citizenship that is classified as a digitania.